PENGARUH PEMBELAJARAN TERPADU TIPE CONNECTED TERHADAP HASIL BELAJAR IPA FISIKA PADA MATERI CAHAYA DAN ALAT OPTIK DI KELAS VIII SMP N 1 SUNGAI TARAB - Dwi Wahyu Oktamagia (Universitas Negeri Padang, 2013)
The low learning outcome of natural science-Physics in junior high school are caused by lack of student’s understanding toward to a concept and student’s inability to think independently. One of the ways to increase students understanding by using the integrated learning type connected. The aim of the research to know the influence of integrated learning type connected toward to natural science-physics outcome in SMP Negeri 1 Sungai Tarab. Research instrument are consist of learning outcome in cognitive domain; observation format in affective domain, and assessment sheet in psychomotor domain. The data analysis by t-test. The result of research are show that there is an effect of integrated learning type connected toward to natural-science physics learning outcome in cognitive and psychomotor domain in significant level 0,05 but not in affective domain. Keywords: Integrated Learning, Connected Type, Science, Optics, Learning Outcomes